Malawi under colonial rule, in Government reports, 1907-1967. - Great Britain. Foreign and Commonwealth Office (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2015)
These records commence at the fracturing of the British Central Africa Protectorate which led to the official formation of the Nyasaland Protectorate. Most records conclude after Nyasaland gained independence in 1964. Nyasaland, now known as Malawi, is never more than one hundred miles wide from west to east and is almost enveloped on three sides by Mozambique, formerly known as Portugese East Africa. The main reason why Nyasaland became a British rather than a Portuguese colonial possession, was that David Livingstone had travelled extensively in the country and written extensively of its potential for Christianity and commerce. His travels were followed by a number of Scottish missionaries who, at the time of the Scramble for Africa, lobbied successfully for the creation of a British administration. In the early years the British Government ruled Nyasaland directly, supplanting local Chiefs in order to assume control. From the 1930's, the Government reversed this decision as they moved to indirect rule and worked with local Chiefs to govern Nyasaland. The work with local Chiefs had limits however and when the Government was faced with opposition to the federation of Nyasaland with Rhodesia in 1953, they proceeded regardless of local protest. The decision to enforce this alliance would hasten the arrival of the call for independence. Commerce and the development of natural resources were key priorities for the colonial government. The Government's most thoroughly documented concern is farming, with surveys of land and water supplies featuring alongside reports on agriculture and veterinary care. Financial returns were also very important to the Government with Estimates, Financial Returns, and Audits featuring alongside Customs and Excise. The Government were particularly keen to ensure that the natives purchased insurance; when the Government found that insurance policies were being mistaken for bank accounts they resolved to educate the population on how to use this financial product. This collection consists of nine groups rather than its original eight, this is because the size of the Natural Resources group was sufficient to require it being split in two.
Date range: 1907-1967.
Keywords: Malawi -- Politics and government -- 20th century